Credibility at stake: seeking the truth in Ian McEwan's Atonement - Abdullah, Omar Mohammed; Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2015)
Ian McEwan is one of the modernist writers who utilises new and uncommon ways of narrating. We find him dealing with history, wars and social themes, all knitted together in a manoeuvring way. The unreliable narrator, a technique he employs, is an innovation first seen in the modern era in Wayne C. Booth's 'The Rhetoric of Fiction' in 1961. McEwan's employment of this technique is an issue needing further analysis. In 'Atonement', his character Briony, who is still a child, narrates parts of the novel but her narration is questioned, for she might not be truthful or honest. Her being unreliable adds much to the novel and affects the fates of her sister Cecelia and the latter's lover, Robbie. It is not only a matter of telling the story, it also interferes in the discourse of the action and propels the events in a different direction. As a result, it seems dubious to give the role of talking to a character (Briony) to narrate and cope with events, and so her telling is questioned to a certain extent because the events she narrates are deceitful on the one hand, while on the other, she is too young and hard to be trusted. The present paper attempts to read 'Atonement' from a new perspective and show what is meant by an unreliable narrator and how this technique is employed. How significant is the technique in terms of recounting the events in a piece of fiction? This paper illustrates the significance of the aforementioned technique, which adds new understanding to the reading of McEwan's 'Atonement'.